Simulasi Dinamis Single Qubit dan Multi Qubit: Sebuah Pendekatan Python - Setyawan, Muhammad Yusril Helmi; Harani, Nisa Hanum; Andriyanto, Achmad (Maranatha University Press, 2025)
This study developed a dynamic simulation system for single qubit and multi qubit using a Python-based approach, leveraging quantum computing libraries such as Qiskit, NumPy, and Matplotlib. The system is designed to simulate various quantum operations, including Hadamard, Pauli-X, Pauli-Y, Pauli-Z, CNOT, and Toffoli, with integration into a Flask-based web interface for easy user interaction. The simulation results show a high level of accuracy, with a difference of only 0.2% in measurement probabilities for single qubit operations like Hadamard and less than 0.4% for multi qubit operations like CNOT and Toffoli. The tests also demonstrated efficient execution times, ranging from 12 to 25 milliseconds, even for complex quantum operations. Validation against established literature confirms that the system is accurate, efficient, and reliable, making it a valuable tool for supporting learning and research in quantum computing.